Geographic variation in suicide rates in Australian farmers: Why is the problem more frequent in Queensland than in New South Wales?. Issue 6 (2nd July 2016) - Arnautovska, Urska; McPhedran, S.; Kelly, B.; Reddy, P.; De Leo, D.
ABSTRACT: Research on farmer suicide is limited in explaining the variations in farmers' demographic characteristics. This study examines farmer suicides in two Australian states: Queensland (QLD) and New South Wales (NSW). Standardized suicide rates over 2000–2009 showed a 2 times higher prevalence of suicide in QLD than NSW (147 vs. 92 cases, respectively). Differences in age and suicide method were observed between states, although they do not appear to account for the sizeable intra- and interstate variations. Suicide prevention initiatives for farmers should account for different age groups and also specific place-based risk factors that may vary between and within jurisdictions.